Rethinking the Urban Community: (Re) Mapping Musical Processes and Places - Kaufman Shelemay, Kay (Lidé města, 2012)
Urban musical research continues to present theoretical and methodological challenges. This paper suggests a revised approach to the study of the urban diaspora community, mapping ways in which musical processes have been instrumental in shaping the cultural places central to the development of the Ethiopian diaspora community. Following cultural geography's attention to "place-making" rather than residential proximity as the locus of community formation, the discussion tracks aspects of musical transmission and performance that have helped generate, shape, and sustain new communities among Ethiopians in the diaspora.